A stochastic downscaling approach for generating high-frequency solar irradiance scenarios. (December 2018) - Zhang, Wenqi; Kleiber, William; Florita, Anthony R.; Hodge, Bri-Mathias; Mather, Barry
Highlights: We stochastically generate 1-min GHI from 30-min satellite estimates. Use a generalized linear model framework that includes non-Gaussian mixtures. Method is validated at numerous sites with different climates throughout the US. Ensembles exhibit good statistical coverages, variability, and autocorrelations. Abstract: Solar power is increasingly cost viable with solar photovoltaic (PV) installations becoming commonplace. PV planning and operational studies, however, require high-frequency solar irradiance scenarios to understand potential electric grid impacts due to the variability and uncertainty of the underlying solar resource. Existing remote sensing solar data products are often available over large spatial domains, but are limited in temporal resolution. For example, the global horizontal irradiance (GHI) component contained within the National Solar Radiation Database (NSRDB) is available at time resolution of 30 min on an approximately four-kilometer grid. In contrast, substantial solar variability is present at finer time scales and this article describes an algorithm to stochastically generate one-minute GHI from widely available sub-hourly NSRDB. A generalized linear modeling (GLM) framework is proposed, which includes non-Gaussian mixtures, and extends the literature involving the synthesis of GHI data. The model is trained on a set of sample locations around Oregon, USA, and validated across the USA using both the Surface Radiation Budget Network (SURFRAD) dataset and Solar Radiation Monitoring Laboratory (SRML) network. Simulated ensembles show good coverage properties and temporal correlation structure. The resulting downscaled ensembles allow for understanding the unpredictable variability inherent in GHI at locations without direct measurements. Future work can leverage the algorithm as part of a stochastic optimization of electric grid operations with high-penetration PV systems.